Human Translation Versus Machine Translation of Instagram’s Captions: Who is the best? - Arvianti, Gilang Fadhilia (Universitas Muhammadiyah Semarang, 2018)
Human translation is different from machine translation. Human translation is judged has better translation than the machine translation. The aim of this paper is to know the difference of human translation compared to machine translation moreover the type of texts to be compared is usingformal and non-formal language. The difference is measured by the quality of human translation which is taken from students‟ translation. The data used in this paper is captions which are written in the Instagram. The captions in Instagram are selected by two topics that cover News item andentertainment since these topics are used in different style of language. The selected captions are translated by university students who have learnt Translation course and by machine which is provided by Instagram itself. The result of those translations is measured by quality assessment byNababan. The result shows that there are differences in human translation and machine translation. Machine translation has good result in translate formal language, then the human translation is good in both formal and non-formal language. It is the evidence that human translation is better than machine translation since human translation is based on some factors in translation.